Prescription patterns of herbal medicine for menopausal disorders in major Korean medicine hospitals: A multicenter retrospective study - Hye Won Lee; Tae-Young Choi; Myeong Soo Lee; Ju Ah Lee; Ji Hee Jun; Jiae Choi; Lin Ang; Chang-Hoon Lee; Jin-Moo Lee; Kyoung Sun Park; Dong Chul Kim; Se-Ran Jang; et al. (Integrative Medicine Research)
Background: This study aimed to obtain the symptom, prescription and therapeutic patterns for the treatment of patients with menopausal syndrome in major Korean medicine (KM) hospitals. Methods: We used a retrospective chart review of climacteric disorder and postmenopausal syndrome patients by examining medical records (ICD-10, menopausal and female climacteric states: N95.1, Menopausal and perimenopausal disorder, unspecified: N95.9) from eight university KM hospitals in South Korea. Results: The main symptoms of 1,682 patients with menopausal disorders visiting 8 college-affiliated oriental medicine hospitals were hot flush, hyperhidrosis, fatigue, insomnia, and chest tightness. Guipi-tang (decoction), Siwu Guipi-tang (decoction), Qingxin Lianzi-yin (decoction), Jiawei Xiaoyao-san (powder) and Guipi Wendan-tang (decoction) were the most commonly prescribed herbal medicines for menopausal disorders. Patients were most often treated with a combination of herbal medicine and acupuncture. Conclusion: Our study shows that the current prescribed herbal medicines were used for treating menopausal disorders in Korean medicine hospitals. However, the objectivity of the efficacy assessment should be studied further.